(untitled) (Swiss Medical Weekly, 2025)
BACKGROUND AND AIMS: Respiratory syncytial virus (RSV) is increasingly recognised as an important cause of respiratory illness in adults. We aimed to analyse clinical and epidemiological characteristics of patients with a positive reverse transcription–polymerase chain reaction (RT-PCR) test in a Swiss regional hospital between 2016 and 2023, including predisposing factors, patient demographics, treatment approaches and clinical outcomes. We also examined temporal patterns of RSV detection during periods of changes in testing strategies and public health measures. METHODS: In this retrospective cohort study at Spital Emmental, we analysed all consecutive in- and outpatients with respiratory symptoms who underwent nasopharyngeal RT-PCR testing following local syndrome-based testing protocols between December 2016 and February 2023. The testing methodology changed from trivalent (influenza A/B, RSV) to quadrivalent (SARS-CoV-2, influenza A/B, RSV) RT-PCR in March 2022, with simultaneous expansion of the testing criteria. Temporal patterns and incidence of positive RSV tests relating to periods of national COVID-19-related public health measures (13 March 2020 and 17 February 2022) were assessed. RESULTS: Of 8135 RT-PCR tests performed, 231 (2.8%) were positive for RSV. The mean age was 69 years, with complete clinical data available for 194 patients. Of these, 157 (81%) required hospitalisation, of whom 19 (12%) were classified as nosocomial infections. Of the hospitalised patients, 14 (9%) required intensive care, with an in-hospital mortality rate of 6%. Major comorbidities in inpatients included cardiac disease (54%), pulmonary disease (49%) and anaemia (43%). Testing patterns showed marked temporal variation: 1766 tests (22%) were performed pre-pandemic, 125 (1%) during pandemic measures and 6244 (77%) after pandemic restrictions were lifted. The introduction of quadrivalent testing in March 2022 led to an increase in testing volume, but lower positivity rates (6% pre- vs 2% post-implementation). CONCLUSIONS: Our results demonstrate RSV-associated resource use and mortality in adults. The temporal evolution of RSV detection in our cohort paralleled changes in testing practices, highlighting the complex interplay between diagnostic strategies and observed disease patterns in a regional hospital setting. Recently introduced preventive vaccination strategies may help to address the impact on patients and healthcare resource utilisation.